Biomaterial-assisted local oxygenation safeguards the prostimulatory phenotype and functions of human dendritic cells in hypoxia - Bhatt, Khushbu; Nukovic, Alexandra; Colombani, Thibault; Bencherif, Sidi A. (Frontiers in Immunology, 2023)
Dendritic cells (DCs), professional antigen-presenting cells, function as sentinels of the immune system. DCs initiate and fine-tune adaptive immune responses by presenting antigenic peptides to B and T lymphocytes to mount an effective immune response against cancer and pathogens. However, hypoxia, a condition characterized by low oxygen (O2) tension in different tissues, significantly impacts DC functions, including antigen uptake, activation and maturation, migration, as well as T-cell priming and proliferation. In this study, we employed O2-releasing biomaterials (O2-cryogels) to study the effect of localized O2 supply on human DC phenotype and functions. Our results indicate that O2-cryogels effectively mitigate DC exposure to hypoxia under hypoxic conditions. Additionally, O2-cryogels counteract hypoxia-induced inhibition of antigen uptake and migratory activity in DCs through O2 release and hyaluronic acid (HA) mediated mechanisms. Furthermore, O2-cryogels preserve and restore DC maturation and co-stimulation markers, including HLA-DR, CD86, and CD40, along with the secretion of proinflammatory cytokines in hypoxic conditions. Finally, our findings demonstrate that the supplemental O2 released from the cryogels preserves DC-mediated T-cell priming, ultimately leading to the activation and proliferation of allogeneic CD3+ T cells. This work emphasizes the potential of local oxygenation as a powerful immunomodulatory agent to improve DC activation and functions in hypoxia, offering new approaches for cancer and infectious disease treatments.